Pengaruh Konflik Kerja dan Stres Kerja Terhadap Kinerja Karyawan Pabrik Rokok Cengkir Gading Nganjuk - Isti'anah, Siti; Wildan, Muhammad Alkirom (Jurnal Kajian Ilmu Manajemen (JKIM), 2023)
ABSTRACTSiti Isti'anah, 2023, The Effect of Work Conflict and Work Stress on Employees Performance At the Cengkir Gading Nganjuk Cigarettes Factory. Guided by Dr. Muhammad Alkirom Wildan, S.E., M.Si.Human resource management has to manage the human resource properly in order to get high quality human resources were needed like as every company needs human resources who perform well to achieve the goals. The purposes were to determine the effect of work conflict and work stress on the employees performance of Cengkir Gading Cigarette Factory, partially and simultaneusly.This study used the associative research using a quantitative approach. Data was collected by the questionnaires from the100 employees as respondents. It used validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression test. Using this analysis, the results showed that 1) the work conflict has a negative and significant effect on employees performance is -0.257, tcount ttable (3.410 1.985), and the significant level is 0.001 0.05. 2) the work stress has a negative and significant effect on employees performance is -0.206, the tcount ttable (2.317 1.985), and the significant level is 0.023 0.05. Then 3) the work conflict and work stress simultaneously have a significant effect on employees performance that Fcount Ftable (8.793 3.94), and the significant level is 0.000 0.05.Keywords: Work Conflict, Work Stress, Employees Performance